Parasitic disease control in a residential facility for the mentally retarded: failure of selected isolation procedures. - Thacker, S B (1981)
Asymptomatic infection with either Entamoeba histolytica or Giardia lamblia was found in 60 per cent of the residents in an institution for the mentally retarded one year after eradication of these parasites. The residents were then segregated into infected and noninfected groups and drug therapy was again successfully undertaken. The two groups remained separated except during periods of play. A one-year follow-up showed that both study and control groups were equally infected. The failure of segregation was confounded by patient age and infection with nonpathogenic parasites.